Pelatihan Smartphone Sehat untuk Orang Tua Di Desa Ngeper - M. Hasan Fahmi; Siti Hadis Sa Ainun Nafiah; Taufik azhary (CV. Agrapana Media, 2025)
Community service activities with the theme 'Healthy Smartphone Training for Parents' in Ngeper Village, Padangan, aim to improve digital literacy and parental awareness in managing smartphone usage wisely within the family environment. The background of this activity is based on the increasing dependence on digital technology among village communities, which has not been matched by the ability to supervise and guide children in using digital devices. The implementation methods include preparation, socialization, interactive training, mentoring, and evaluation stages, designed participatively. The results of the activity show an increase in participants' understanding of the risks and benefits of smartphone use, the ability to manage screen time, as well as skills in applying digital control and supervision. In addition, the formation of the Healthy Digital Care Group serves as a sustainable program that strengthens the digital literacy culture within the community. This activity makes a tangible contribution to building digitally smart families who are adaptive to technological developments, while still upholding ethical values and social responsibility.